The art of war: using genetic insights to understand and harness radiation sensitivity in hematologic malignancies - Wijetunga, N. Ari; Yahalom, Joachim; Imber, Brandon S. (Frontiers in Oncology, 2025)
It is well established that hematologic malignancies are often considerably radiosensitive, which enables usage of far lower doses of therapeutic radiotherapy. This review summarizes the currently known genomic landscape of hematologic malignancies, particularly as it relates to radiosensitivity and the field of radiation oncology. By tracing the historical development of the modern understanding of radiosensitivity, we focus on the discovery and implications of pivotal mutated genes in hematologic malignancies such as TP53, ATM, and other genes critical to DNA repair pathways. These genetic insights have contributed significantly to the advancement of personalized medicine, aiming to enhance treatment precision and outcomes, and there is an opportunity to extend these insights to personalized radiotherapy. We explore the transition from early discoveries to the current efforts in integrating comprehensive genomic data into clinical practice. Specific examples from Hodgkin lymphoma, non-Hodgkin lymphoma, and plasma cell neoplasms illustrate how genetic mutations could influence radiosensitivity and impact subsequent radiotherapeutic response. Despite the advancements, challenges remain in translating these genetic insights into routine clinical practice, particularly due to the heterogeneity of alterations and the complex interactions within cancer signaling pathways. We emphasize the potential of radiogenomics to address these challenges by identifying genetic markers that predict radiotherapy response and toxicity, thereby refining treatment strategies. The need for robust decision support systems, standardized protocols, and ongoing education for healthcare providers is critical to the successful integration of genomic data into radiation therapy. As research continues to validate genetic markers and explore novel therapeutic combinations, the promise of personalized radiotherapy becomes increasingly attainable, offering the potential to significantly improve outcomes for patients with hematologic malignancies.